Effect of Pretreatment on Germination Enhancement of Tephrosia candida (Roxb.) DC Seed - Bahar, Nawa (Indian Forester, 2015)
Tephrosia candida is an excellent nitrogen fixing green manure yielding species, which produces hard-coated and green black colour seeds. Seed has physical dormancy due to hardiness of testa. Suitable pretreatment to break the dormancy was investigated. Germination was enhanced from 22.77 per cent (untreated) to 90.14 per cent (mechanical scarification). Although, mechanical scarification treatment gave early, uniform and highest germination, but it is not practicable on large-scale. Therefore, hot water soaking for 24 hours or scarification by sulphuric acid for 15 minutes is recommended.